PTP1B-Mediated Dephosphorylation of SRC Controls Fibrogenic Cellular Activation - Bootsakorn Boonkaew; Nuchanart Suntornnont; Chaiyaboot Ariyachet (Emerging Science Journal, 2026)
Liver fibrosis, the precursor to cirrhosis and hepatocellular carcinoma (HCC), represents a global health crisis with millions affected and few effective treatments available. This progressive pathology is characterized by excessive extracellular matrix (ECM) deposition, primarily driven by the activation of hepatic stellate cells (HSCs) into profibrogenic myofibroblasts. Elucidating the molecular control of HSC activation is paramount for therapeutic development. Protein-tyrosine phosphatase 1B (PTP1B), an established target in metabolic diseases, has emerging pro-fibrotic roles, as evidenced by protection against liver fibrosis in PTP1B-deficient mice. However, the regulatory function of PTP1B in human-relevant models remains poorly understood. Here, we define the role and mechanistic significance of PTP1B in primary human HSCs and investigate its clinical relevance in human fibrotic liver. Using loss- and gain-of-function approaches in primary human HSCs, we demonstrate that PTP1B significantly promotes HSC activation, evidenced by enhanced proliferation, migration, and increased expression of key ECM genes and collagen production. Mechanistically, PTP1B acts as a positive regulator of the pro-fibrotic SRC kinase, directly dephosphorylating the inhibitory tyrosine 527 (Y527) residue to induce its activation. Pharmacological inhibition of SRC effectively reversed the PTP1B-driven pro-fibrotic phenotypes. Consistent with our findings, re-analysis of human fibrotic liver tissues revealed that PTP1B and SRC expressions are significantly upregulated and positively correlated with ECM genes. Collectively, these findings establish a novel PTP1B-SRC signaling axis that critically drives human HSC activation and hepatic fibrogenesis, positioning PTP1B as a high-potential therapeutic target for liver fibrosis.